Opioid Therapy for Chronic Nonmalignant Pain - Russell K Portenoy (Pain Research and Management)
Long term administration of an opioid drug for chronic nonmalignant pain continues to be controversial, but is no longer uniformly rejected by pain specialists. This is true despite concerns that the regulatory agencies that oversee physician prescribing of opioid drugs continue to stigmatize the practice. The changing clinical perspective has been driven, in part, by widespread acknowledgement of the remarkably favourable outcomes achieved during opioid treatment of cancer pain. These outcomes contrast starkly with popular teaching about chronic opioid therapy and affirm the potential for prolonged efficacy, tolerable side effects, enhanced function associated with improved comfort and minimal risk of aberrant drug-related behaviours consistent with addiction. A large anecdotal experience in populations with nonmalignant pain suggests that these patients are more heterogeneous and that opioid therapy will greatly benefit some and will contribute to negative outcomes for others. The few controlled clinical trials that have been performed support the safety and efficacy of opioid therapy, but have been too limited to ensure generalization to the clinical setting. A critical review of the medical literature pertaining to chronic pain, opioid pharmacology and addiction medicine can clarify misconceptions about opioid therapy and provide a foundation for patient selection and drug administration. The available data support the view that opioids are no panacea for chronic pain, but should be considered in carefully selected patients using clinically derived guidelines that stress a structured approach and ongoing monitoring of efficacy, adverse effects, functional outcomes and the occurrence of aberrant drug-related behaviours.